Response of Seed Dressing With Boron Dust and Slurry on Wheat Variety WK- 1204 For Grain Yield and Agronomic Traits under Poly Bag and Field Study At Khumaltar, Nepal - Paudel, Mina Nath (Agronomy Journal of Nepal, 2016)
Field and poly bag experiments were carried out at Khumaltar on wheat variety WK-1204 by dressing seed with sodium borate decahydrate dust (containing 11.34% elemental boron) and slurry per 100 g wheat seed. A total of nine treatments of Boron (B) dust and slurry to treat wheat seed at 2.2, 4.4, 6.4 and 8.8 gram per 100 g seed and basal application of B at 1.0 kg a.i./ha was in three replications for both field and poly bag experiments in randomized complete block design. The objective of the study was to find out the effect of boron seed dressing on grain yield and agronomic attributes of wheat variety under study. The result of the study revealed that grain yield and agronomic traits were highly and significantly correlated with seed dressing with boron dust at 2.2 to 8.8 g boron /100 g seed of wheat. This finding was consistent with field and poly bag experiments which were coherent with the findings of lab analysis for attributes of root and shoot length, and percentage of germination. However, seed dressing with boron slurry at 2.2 to 8.8 g/ 100 g wheat seed inhibited grain yield and agronomic attributes of wheat in the study. Therefore, seed dressing with boron dust at different level was superior over seed dressing with boron slurry for higher grain yield and yield related traits of wheat variety WK-1204 at Khumaltar condition. Boron deficiency for wheat could be corrected by seed dressing with boron dust at 2.2 to 8.6 g boron /100g wheat seed. This could be very economical and practical way of enhancing wheat production in hilly terrain areas of Nepal where one of the reasons of yield limitations is due to deficiency of boron.Agronomy Journal of Nepal (Agron JN), Vol.4, 2016, page: 64-74